2012
DOI: 10.1007/s12052-012-0399-9
|View full text |Cite
|
Sign up to set email alerts
|

Changing Museum Visitors’ Conceptions of Evolution

Abstract: We examined whether a single visit to an evolution exhibition contributed to conceptual change in adult (n = 30), youth, and child (n = 34) museum visitors’ reasoning about evolution. The exhibition included seven current research projects in evolutionary science, each focused on a different organism. To frame this study, we integrated a developmental model of visitors’ understanding of evolution, which incorporates visitors’ intuitive beliefs, with a model of free-choice learning that includes personal, socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 48 publications
8
64
1
6
Order By: Relevance
“…Despite its fundamental importance in biology and many other research fields, studies have shown that biological evolution is not yet accepted as a valid scientific theory by an important fraction of citizens from different nations (Miller et al 2006), and that misconceptions about evolution are frequent and shared by the general public, students, and teachers from several countries (Rutledge and Warden 2000;Nehm and Reilly 2007;Prinou et al 2011;Spiegel et al 2012). Furthermore, these misconceptions revealed to be persistent and difficult to overcome, even when applying learning programs specifically designed to promote such conceptual changes (Bishop and Anderson 1986;Nehm and Reilly 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its fundamental importance in biology and many other research fields, studies have shown that biological evolution is not yet accepted as a valid scientific theory by an important fraction of citizens from different nations (Miller et al 2006), and that misconceptions about evolution are frequent and shared by the general public, students, and teachers from several countries (Rutledge and Warden 2000;Nehm and Reilly 2007;Prinou et al 2011;Spiegel et al 2012). Furthermore, these misconceptions revealed to be persistent and difficult to overcome, even when applying learning programs specifically designed to promote such conceptual changes (Bishop and Anderson 1986;Nehm and Reilly 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid this problem, a straightforward measure of acceptance that does not also measure understanding of evolutionary facts was used in this study (see Spiegel et al 2012). Acceptance was operationalized as the extent to which a student agrees that evolutionary processes explain the origin of diverse species, including humans, as this contentious issue is the one most likely to challenge religious belief and individual identity.…”
Section: Belief Understanding Acceptance and Knowledgementioning
confidence: 99%
“…This was based on a measure validated in Spiegel et al (2012), which explored whether visitors to a museum changed their conceptions of evolution following their exposure to an exhibit on evolution. Most of the variables in the Spiegel et al (2012) study were based on open-ended scenarios, but the visitors were also asked the same three Likert scale questions on their acceptance of evolutionary origins as in the current study, though the organisms differed, being insects, birds, and humans.…”
Section: Validity and Reliabilitymentioning
confidence: 99%
“…. .naturally biased to view nature as though it is intentionally created', [8], p. 77), has resonated throughout the cognitive sciences, influencing interpretations of concept development [9][10][11][12][13] science learning [8,14], religion and morality [15][16][17][18][19][20], and cross-cultural reasoning [7].…”
Section: Are Clouds 'For' Raining?mentioning
confidence: 99%